# 115 = (5x-2)(2x)/2          The numerator is the equation (5x-2) (2x) and the denominator is 2.

Posted on

`115 = ((5x-2)(2x))/2`

`115*2 = (5x-2)(2x)`

`230 = 10x^2-4x`

`10x^2-4x-230 = 0`

Dividing both sides by 2.

`5x^2-2x-115 = 0`

The solution for the above equation is;

`x = ((-2)+-sqrt((-2)^2-4*5*(-115)))/(2*5)`

x = 5 or x = -4.6

So the answers are x = 5 or x = -4.6

Posted on

115=(5x-2)(2x)/2

First thing is first:  GET RID OF THE FRACTION (5x-2)(2x)/2

-> Multiply both sides by the reciprocal of the denominator to get rid of a fraction. In this problem the fraction is really 1/2, so multiply both sides by 2/1 or 2.

115*2=(5x-2)(2x)/2 *2

2/1*1/2=1 so now there is no more fraction.

115*2=230

Now rewrite the problem:

230=(5x-2)(2x) -->multiply 2x*5x=10x^2, 2x*-2=-4x

Now rewrite the problem:

230=10x^2-4x  --> subtract 230 from both sides

-230          -230

Rewrite the problem:

0=10x^2-4x-230  -->simplify!

0=5x^2-2x-115

-->Now you have to figure out what x equals!